Design and development of wireless charging system for electric vehicles in Singapore - Tan, Dylan Wei Jian (2018)
The concept of wireless charging has been around for decades. From 1880s where Nikola Tesla illuminated phosphorescent lamps wirelessly till wireless charging in our devices today. Many mobile phones manufacturers today are pushing for wireless charging. Apple and Samsung both offer such capabilities in their latest line-up of phones. The trend of Wireless charging is also progressing in large-scale application such as in electric vehicles (EVs). EVs are increasingly more popular in recent years due to concern of oil prices and the environment. Naturally, with this effect, there needs to be improvement and development of charging infrastructures to support EVs. “Plug-in” systems could be a solution however, owners are required to remember to plug in the charger and “Plug-in” systems take up space. Therefore, there needs to be a more convenient and efficient way to recharge these EVs. Dynamic wireless charging is one such way. Having a sharing network of wireless chargers built into roads will not only allow for convenient charging but also eliminate the need for charging stations that take up space. In the report, investigation of using resonant charging as a method for wireless charging in EVs will be conducted. 3 key metrics will be used to draw comparison between this mode of wireless charging and current methods. Upon establishment of the benefits of resonant charging over current methods, this report outlines a proof of concept of the implementation of such wireless charging in a small-scale model. The circuits in this report employs the use of DC/AC oscillators, resonating capacitors, AC/DC rectifiers and DC/DC buck converters. The 3-key metrics that will be examined in the report are; charging distance, misalignment of coils and object interference. The proof of concept model will be used to illustrate the use of resonant charging method to implement dynamic wireless charging systems on roads.